DOES EXECUTIVE COMPENSATION EFFECT ON HUMAN RESOURCE QUALITY STUDY FROM STATE-OWNED ENTERPRISES IN INDONESIA - Nur Wachidah Yulianti (Universitas Sarjanawiyata Tamansiswa, 2022)
According to the explanation of Republic of Indonesia Law No. 19 of 2003 concerning State-Owned Enterprises (SOE), that is SOE have not been able to compete in global business competition because the company's performance is considered inadequate, seen from the low profit earned compared to the invested capital, then SOE have not been able to provide goods or services of high quality to the community at an affordable price. It is a challenge that must be faced by SOE companies in Indonesia to improve the development of the quality of Human Resources (HR). A chief Executive Officer (CEO) may work on how to build teams to success and must be understand how to improve the abilities of his employees. Compensation is the final piece from CEOs in order to empower its employee. The result of this research concludes that executive compensation positive significantly effect to training and education provided to employee as an effort to improve human resource quality.